(untitled) (INNOVATIVE ECONOMY, 2024)
Shymanska O.P., Teliuk D.T. THE STATE AND PROSPECTS OF THE DEVELOPMENT OF CRYPTOCURRENCIES IN THE DIGITAL ECONOMY Purpose. The aim of the article is to determine the place of cryptocurrencies in the digital economy, assess their state and development trends, research prospective directions for expanding the scope of their use by introducing innovative technologies and tools, and reducing the risks of investing in crypto assets. Methodology of research. The following research methods were used to achieve the set goal: induction and deduction – in the process of identifying cause-and-effect relationships and trends in the development of cryptocurrencies in the digital economy; analysis and synthesis – in the process of studying the individual essential characteristics of the category "cryptocurrency"; comparison – in the process of researching changes in the market capitalization of cryptocurrencies, the dynamics of the Bitcoin exchange rate, the dynamics of the market capitalization of cryptocurrencies and DeFi; graphic – to visualize the results of the study. Findings. The influence of environmental factors on the dynamics of the development of cryptocurrencies during 2021‒2023 has been determined. The directions of their development in the digital economy are substantiated, which include the correlation of the crypto market with traditional markets and the financial sector of the economy, the emergence of new types of cryptocurrencies that expand the range of offered market tools, the expansion of the scope of use of cryptocurrencies through the introduction of innovative technologies and tools. Alternative directions for investing in crypto assets have been identified. A comparative assessment of the risks of traditional investing and investing in cryptocurrencies was carried out. Originality. Determining the essential characteristics of cryptocurrencies, such as price volatility, investment attractiveness and riskiness, has been further developed. Prospective directions for the use of innovative tools in the crypto industry, in particular, decentralized finance (DeFi), are substantiated. Practical value. Conclusions and proposals substantiated by the results of the research can be used in the process of carrying out operations with cryptocurrencies and making decisions by market subjects regarding directions and instruments for investing in crypto assets. Key words: cryptocurrencies, market capitalization, rate dynamics, price volatility, innovative technologies and tools in the crypto industry, decentralized finance (DeFi), alternative investments in crypto assets.